Synergy in Efficacy of Artemisia sieversiana Crude Extract and Metarhizium anisopliae on Resistant Oedaleus asiaticus - Li, Shuang; Xu, Chaomin; Du, Guilin; Wang, Guangjun; Tu, Xiongbing; Zhang, Zehua (Frontiers in Physiology, 2021)
In order to explore the synergistic control effect of crude extracts of Artemisia sieversiana and Metarhizium anisopliae on Oedaleus decorus asiaticus, we used different doses of M. anisopliae and crude extracts of A. sieversiana singly and in combination, to determine their toxicities to fourth instar O. asiaticus. The results showed that the combination of 10% crude extract of A. sieversiana with 107 and 108 spores/g M. anisopliae concentrations and the combination of 20% crude extract of A. sieversiana with 107 and 108 spores/g M. anisopliae concentrations had significant effects on the mortality, body weight gain, body length gain, growth rate and overall performance of O. asiaticus than those of the crude extract of A. sieversiana and M. anisopliae alone. Among them, the 20% A. sieversiana crude extract mixed with 108 spores/g M. anisopliae and 10% A. sieversiana crude extract combined with 107 spores/g M. anisopliae, had the best control efficacy. In order to clarify the biochemical mechanism underlying the immune responses of O. asiaticus to the pesticide treatments, we monitored the activities of four enzymes: SOD, POD, CAT and PPO. The results showed that the activities of three enzymes (SOD, CAT and PPO) were significantly increased from the treatment with the combination of M. anisopliae mixed with crude extract of A. sieversiana. Interestingly, compared to the crude extract, the combination treatment did not significantly induce the expression of POD enzyme activity, which may be a biochemical factor for increasing the control effect of the combination treatment. Our results showed that the combination treatment had synergistic and antagonistic effects on host mortality, growth, development and enzyme activities in O. asiaticus.